2009
DOI: 10.1183/09031936.00121608
|View full text |Cite
|
Sign up to set email alerts
|

Optimal positive airway pressure predicts oral appliance response to sleep apnoea

Abstract: Patients with less severe obstructive sleep apnoea (OSA) are usually prescribed oral appliances and/or smaller optimal nasal continuous positive airway pressure (PnCPAP) in nCPAP therapy. We hypothesised that OSA patients with greater PnCPAP would not respond favourably to oral appliances.Oral appliances were inserted in nCPAP users after washing-out the nCPAP effect. Follow-up polysomnography was undertaken with the adjusted oral appliance in place. The predictability of PnCPAP was evaluated with receiver-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 37 publications
7
58
1
Order By: Relevance
“…Our findings lend support to the previously reported relationship between CPAP pressure and MAS treatment response, 9 and extend these findings by identifying a much higher CPAP pressure cutoff for negative prediction of MAS response in this population. The implication is that there may be populationspecific characteristics that influence the cutoff pressure values for which CPAP is best predictive of MAS response.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings lend support to the previously reported relationship between CPAP pressure and MAS treatment response, 9 and extend these findings by identifying a much higher CPAP pressure cutoff for negative prediction of MAS response in this population. The implication is that there may be populationspecific characteristics that influence the cutoff pressure values for which CPAP is best predictive of MAS response.…”
Section: Discussionsupporting
confidence: 90%
“…Differences in the relationship between CPAP pressure and MAS response may relate to these different hard and soft tissue proportions. BMI was lower in MAS responders in our study and was a predictor of response in univariate analyses (data not shown); however, no such relationship was evident in the Japanese study, 9 suggesting obesity was less of a factor in MAS treatment response. BMI and neck circumference also relate to CPAP pressure in Caucasian populations.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The same author in 2009 showed that it is possible to optimize MRA results by increasing mandibular advancement during a polysomnographic titration in patients with an incomplete response to treatment [33]. Tsuiki et al [34] observed better results with MRA in patients who had required CPAP pressure below 10.5 cmH2034. Despite these several possible predictors of success for MRA in the treatment of OSA already described in the literature, they are still not definitive, since the studies present differences in the criteria of success adopted, in the design of the employed MRA, in the configuration of the samples (age, BMI, cervical circumference, pre-treatment AHI, gender) and in the final mandibular position reached thus affecting the results obtained [35].…”
Section: Predictors Of Successmentioning
confidence: 99%